2020
DOI: 10.1167/jov.20.8.26
|View full text |Cite
|
Sign up to set email alerts
|

From Gaussian blobs to naturalistic videos: Comparison of oculomotor behavior across different stimulus complexities

Abstract: Research on eye movements has primarily been performed in two distinct ways: (1) under highly controlled conditions using simple stimuli such as dots on a uniform background, or (2) under free-viewing conditions with complex images, real-world movies, or even with observers moving around in the world. Although both approaches offer important insights, the generalizability among eye movement behaviors observed under these different conditions is unclear. Here, we compared eye movement responses to video clips s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 87 publications
(114 reference statements)
0
10
0
Order By: Relevance
“…Motion characteristics of noise dots in an RDK, together with their lifetime, affect the perception of global motion as well as pursuit quality (Pilly and Seitz 2009;Schütz et al 2010). Future work is needed to elucidate the potential influence of the characteristics of sensory stimuli-ranging from simplified dots, blobs and RDKs to more complex naturalistic stimuli (Goettker et al 2020)-on behavioral biases in perception and eye movements.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Motion characteristics of noise dots in an RDK, together with their lifetime, affect the perception of global motion as well as pursuit quality (Pilly and Seitz 2009;Schütz et al 2010). Future work is needed to elucidate the potential influence of the characteristics of sensory stimuli-ranging from simplified dots, blobs and RDKs to more complex naturalistic stimuli (Goettker et al 2020)-on behavioral biases in perception and eye movements.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…For instance, Debono et al (2010) defined an “oculoceptive” field driving human steady-state pursuit with spatial extent (<10°) that matches the present results. Moreover, for voluntary pursuit, these spatial properties are often modulated by contextual effects such as the structure ( Masson et al, 1995 ; Spering and Gegenfurtner, 2007 ) and richness of the visual scene ( Goettker et al, 2020 ), feature motion saliency, and spatial attention (for review, see Souto and Kerzel, 2021 ). Simple tracking responses such as ocular following can efficiently complement these approaches, with the opportunity to map with high spatial and temporal resolution the different preattentive mechanisms operating at different spatial and temporal scales and link them to basic physiological mechanisms along the primate motion pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Smooth eye movements have received less attention. Some previous studies have reported a useful role for smooth pursuit during perceptual or visuomotor tasks ( Cesqui et al, 2015 ; Danion & Flanagan, 2018 ; Spering et al, 2011 ), others have reported the occurrence of spontaneous smooth pursuit ( Brenner & Smeets, 2011 ; Corrigan et al, 2017 ; Dorr et al, 2010 ; Goettker et al, 2020 ; Land & McLeod, 2000 ; Lappi et al, 2013 ; Ross & Kowler, 2013 ), and still others have not reported changes in smooth eye movements, despite the fact that key objects were continually in motion ( Johansson et al, 2001 ; Ko et al, 2010 ; Kowler et al, 2014 ). The present study sought to better understand eye movement strategies during dynamic perceptual tasks, with an emphasis on the involvement of smooth eye movements, including their role as indicators of the distribution of attention over time.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have focused on the occurrence or value of smooth eye movements during active, dynamic perceptual or visuomotor tasks involving moving objects. Smooth pursuit has been reported to occur while watching videos ( Corrigan, Gulli, Doucet, & Martinez-Trujillo, 2017 ; Dorr, Martinetz, Gegenfurtner, & Barth, 2010 ; Goettker, Agtzidis, Braun, Dorr, & Gegenfurtner, 2020 ; Ross & Kowler, 2013 ) or driving ( Lappi, Pekkanen, & Itkonen, 2013 ); however, in these studies, the pursuit was not explicitly related to performance of a task. One example in which smooth pursuit was related to visual performance is Spering, Schütz, Braun, and Gegenfurtner (2011) , who studied the role of smooth pursuit when judging whether a moving target on one side of a display would hit a stationary target on the other side.…”
Section: Introductionmentioning
confidence: 94%